Separation of geraniol from citronellol by selective oxidation of geraniol to geranial - Chong, Daniel Jun Weng; Jalifah Latip; Siti Aishah Hasbullah; Sastrohamidjojo, Harjono (Universiti Kebangsaan Malaysia, 2015)
Rhodinol is a mixture of geraniol and citronellol. It is the second fraction in fractional distillation of commercially grown Cymbopogon nardus. The physical and chemical similarities of these two compounds made them inseparable. The individual use of each compound is of great importance. A selective oxidation (hydrogen peroxide activated by platinum black) of geraniol (in rhodinol) to geranial was done while remaining citronellol intact in order to separate the two compounds into different chemical functionality. A yield of 81% geranial achieved while minimizing citronellal formation from citronellol to 17%. Chemical separation using sodium hydrogen sulfite (NaHSO3) was done to separate the aldehydes from the unreacted citronellol. Purification using fractional distillation was done to obtain pure geraniol and remove minor fraction of citronellal.